2015
DOI: 10.1007/s12192-014-0548-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression, function, and regulation of the testis-enriched heat shock HSPA2 gene in rodents and humans

Abstract: The HSPA2 gene is a poorly characterized member of the HSPA (HSP70) family. HSPA2 was originally described as testis-specific and expressed at the highest level in pachytene spermatocytes of rodents, the expression of which is not induced by heat shock. HSPA2 is crucial for male fertility. However, recent advances have shown that HSPA2 is expressed in various tumors and in certain types of somatic tissues. In this review, we summarize the current knowledge on the HSPA2 expression pattern, including information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 104 publications
1
47
0
Order By: Relevance
“…Several of these RHOX-regulated genes have been shown to have crucial roles in human male reproduction. For example, idiopathic infertile men who completely lack HSPA2 in their sperm exhibit impaired fertilizing ability (31,34) and reduced expression of HSPA1A in ejaculated sperm has been implicated in the pathogenesis of male infertility (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these RHOX-regulated genes have been shown to have crucial roles in human male reproduction. For example, idiopathic infertile men who completely lack HSPA2 in their sperm exhibit impaired fertilizing ability (31,34) and reduced expression of HSPA1A in ejaculated sperm has been implicated in the pathogenesis of male infertility (35).…”
Section: Discussionmentioning
confidence: 99%
“…A subset of 8 candidate genes, composed of the 5 most strongly regulated genes (ANKRD1, DNAJB1, HSPA6, HSPH1, RHOXF1) and 3 regulated genes that have been previously associated with human fertilization (HSPA1A; (29,30) and abnormal spermatogenesis (HSPA2, MSH5; (31,32), were selected for validation by qRT-PCR analysis.…”
Section: Identification Of Genes Regulated By Rhox Transcription Factorsmentioning
confidence: 99%
“…Recently, HSPA2 in particular has been recognized as a key regulator of spermatocyte maturation and function. HSPA2 deficiency has been found in infertile men, and lower levels of HSPA2 predicted assisted reproductive technology failure (reviewed in Scieglinska and Krawczyk 2015).…”
Section: Gametogenesismentioning
confidence: 99%
“…This classification was justified due to the genes' high expression in pachytene spermatocytes and fertility impairment of male but not female hsp70.2 knockout mice (for review see [1]). Initial work on human HSPA2 revealed that its transcript is abundant not only in the testes but also in some other tissues [2].…”
Section: Introductionmentioning
confidence: 99%
“…Deletion analysis of the HSPA2 promoter determined that the 400 bp DNA fragment localized upstream of the ATG codon is sufficient to support reporter gene expression in cancer cells [12]. HSPA2 expression is not induced by heat shock [6; 9], and it is not clear whether transcription of this gene can be modulated by any other form of cellular or environmental stress (see [1] for a comprehensive review of HSPA2). Huang et al [13] reported that HSPA2 can be upregulated by hypoxia in the cancer cell lines HepG2, MCF-7, and HeLa.…”
Section: Introductionmentioning
confidence: 99%